Spiritual Journey Principles in Javanese House: An Interdisciplinary Reading - Wismantara, Pudji Pratitis (UIN Maulana Malik Ibrahim Malang, 2011)
Re-contextualizing effort is begun by formulating basic character then developing of architectural design. The purpose of this paper is to explore and re-contextualize the basic character of traditional Javanese house. This study used visual culture method as a thorough of the architectural form and substance behind it by including inter-disciplinary scientific approach. The first step is tracing equivalence thought expression among traditional Javanese House and other traditional houses in through Indonesian archipelago, such as Aceh, Toraja, and Dayak, by doing trans-cultural readings. Step two, is finding a relationship between traditional Javanese house with non-architectural folklore, for instance the story of Dewa Ruci and serat Jatimurti, by doing trans-structural readings. In the process of study, it is seen that traditional Javanese house is consist of universal characters and Javanese local characters. The structural space on the traditional Javanese house is relevance to the concept of Islamic journey that negating god other than Allah, and travelling towards Allah. The discovery of the thought expression which is the basic character of this traditional Javanese house, at least, can be a starting point in developing an architecture which is suitable for the space context (of Java) and time context (present). Upaya rekontekstualisasi dimulai dengan merumuskan karakter dasar dan dilanjutkan dengan membangun rancangan arsitekturalnya. Tujuan paper ini adalah untuk mengeksplorasi dan merekontekstualisasi karakter dasar pada Rumah Adat Jawa. Model pengkajiannya menggunakan metode visual culture, sebagai model pembacaan menyeluruh terhadap wujud arsitektur dan substansi di baliknya, dengan menyertakan pendekatan antardisiplin keilmuan. Langkah pertama, melacak kesepadanan ungkapan pemikiran antara Rumah Adat Jawa dengan Arsitektur lain di wilayah Nusantara, seperti Aceh, Toraja, dan Dayak, dengan melakukan pembacaan lintas-kultural. Langkah kedua, mencari korelasi antara Rumah Jawa dengan folklore non-arsitektural, seperti kisah Dewa Ruci dan Serat Jatimurti, dengan melakukan pembacaan lintas-struktural. Dalam proses kajian dapat ditunjukkan bahwa Rumah Adat Jawa memiliki karakter universal Nusantara dan karakter lokal Jawa. Perjenjangan ruang pada Rumah Jawa memiliki keterkaitan dengan konsep perjalanan meniadakan selain Allah, dan perjalanan menuju kepada Allah. Penemuan ungkapan pemikiran, yang merupakan karakter dasar Rumah Jawa ini, setidaknya bisa menjadi landasan pijak dalam mengembangkan arsitektur, yang sesuai dengan konteks ruang (Jawa) dan konteks waktu (kekinian).